Indonesia ANALISIS DAYA DUKUNG LINGKUNGAN DAN STATUS KEBERLANJUTAN WISATA OBYEK MATA AIR COKRO TULUNG, KABUPATEN KLATEN: ANALISIS DAYA DUKUNG LINGKUNGAN DAN STATUS KEBERLANJUTAN WISATA OBYEK MATA AIR COKRO TULUNG, KABUPATEN KLATEN - Sunarto; Eli Santika, Youhana; Prabang, Setyono (Prodi Kehutanan Universitas Khairun, 2025)
The Cokro Spring Object still tends to be directed towards mass tourism where this tourism has a strategy to accelerate tourist visits through tourism products that are popular with visitors without considering all the potential that will occur so that there is the potential for environmental problems. Therefore, research is needed related to the Environmental Carrying Capacity and Tourism Sustainability Status as a basis for determining the development strategy of the Cokro Spring Object. The purpose of this study was to determine the environmental carrying capacity of the Cokro Spring Object Tourism, to determine the sustainability status of the Cokro Spring Object Tourism, and to determine the development strategy of the Cokro Spring Object Tourism. The research method used primary data collection in the form of observation, questionnaires, and interviews, while secondary data was in the form of journal and document literature studies. Data analysis used the Cifuentes Method to calculate the carrying capacity of the tourism environment, the Rap-Tour Method (Rapfish Modified) to determine the status of tourism sustainability, and SWOT Analysis through IFAS and EFAS calculations with the results of the grand strategy graph quadrant for the basis of tourism development strategies. The results of the study showed that the value of the physical carrying capacity was 1958 people/day, the real carrying capacity was 243 people/day, and the effective carrying capacity was 207 people/day. The large value of PCC>RCC>ECC means that the Cokro Spring Tourism Object can still be developed. The results of the multidimensional Tourism Sustainability Status are included in the Sustainable Enough category with an index of 70.9301%. The Cokro Spring Tourism Object Development Strategy is located in quadrant I, the S-O strategy is carried out by increasing the intensity of tourism promotion, establishing cooperation with the tourism office and the private sector through the addition of educational tourism activities or attractions, involving local communities through the creation of integrated tourism packages, and maintaining the condition of natural water resources in tourism development.